Identification of factors influencing tampering of codeine-containing medicines in England: a qualitative study - Andreas Kimergård; Stephen Parkin; Stacey Jennings; Eileen Brobbin; Paolo Deluca (BMC, 2020)
Abstract Background Tampering of psychoactive medicines presents challenges to regulation and public health. However, little is currently known about what influences the decisions to treat codeine-containing medicines (CCM) with cold water extraction (CWE) from the perspective of individuals employing these techniques. The article identifies factors influencing utilisation of CWE to separate codeine from compounded analgesics, such as paracetamol and ibuprofen, found in CCM. Methods Purposive sampling of 27 participants residing in England who took part in a qualitative interview. Of these, 14 individuals (11 males and 3 females) reported tampering of psychoactive medicines, and the relevant transcripts were included in the analyses for the study. Participants were recruited from one addiction treatment service and from an online survey. The mean age of the participants was 31.5 years (range = 18-42 years). Qualitative data analysis followed the processes of iterative categorization (IC). The codes 'harm reduction', 'information sources' and 'changes on the drug markets' were grouped and summarised. The coding of the data was done in a Microsoft® Word document. Results Two groups of participants were identified in the data analysis: (i) individuals who used CCM (n = 5), and (ii) individuals who used CCM and heroin (n = 9). Participants in both groups used CWE due to concerns of paracetamol overdose from the use of excessive dosages of CCM. For both of them, information obtained from the internet encouraged the use of CWE. Participants using CCM described how the many steps involved in conducting CWE, including sourcing codeine boxes from pharmacies (over the counter), presented a barrier against using CWE. Participants using CCM and heroin explained how reduced availability in the local heroin supply influenced utilisation of CWE techniques to maintain their use of opioids and avoid withdrawal. Withdrawal symptoms and cravings outweighed the concerns about the quality of the extracted codeine mixtures in this participant group, especially the ability of CWE to remove paracetamol and tablet fillers. Conclusions Utilisation of CWE of codeine was influenced by several factors including drug market supply, the availability of detailed information on the internet about CWE and restrictions on codeine sourcing in pharmacies. Risks identified with CWE include consumption of unknown doses of paracetamol if the CWE techniques are not used correctly. Attempts at extracting codeine from CCM should be considered in risk assessments of opioid medicines.